Spacelike hypersurfaces with constant mean curvature in the steady state space - Colares, Antônio Gervásio (2010)
COLARES, Antônio Gervásio ; LIMA, Henrique Fernandes de. Spacelike hypersurfaces with constant mean curvature in the steady state space. Bulletin of the Belgian Mathematical Society Simon Stevin, v. 17, p. 287-302, 2010.